2016
DOI: 10.1007/s00267-016-0793-0
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Post-Fire Plant Cover in the Performance of Two Cordilleran Cypress (Austrocedrus chilensis) Seedling Stocktypes Planted in Burned Forests of Northeastern Patagonia, Argentina

Abstract: Cordilleran cypress (Austrocedrus chilensis [D.Don] Pic. Serm. et Bizarri) forests occupy 140,000 ha along a sharp environmental gradient of central Andean-Patagonia in Argentina. Every summer, about 3200 ha of these forests are affected by wildfires, taking thereafter long time to recover. To accelerate forest recovery, we determined in xeric and mesic cypress stands burned 5 and 2 year before whether survival and growth of two planted cypress seedling stocktypes are affected by plant cover and contrasting pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 26 publications
0
5
0
4
Order By: Relevance
“…However, competition might affect growth in a great variety of ways, and it may differ among communities (Reader et al 1994). In a mesic area similar to our study site, A. chilensis seedling survival and growth were positively associated with post-fire cover during the 2 years after plantation (Urretavizcaya et al 2017). In our study, however, this nursing effect appeared two seasons after acclimation.…”
Section: Discussionmentioning
confidence: 45%
See 1 more Smart Citation
“…However, competition might affect growth in a great variety of ways, and it may differ among communities (Reader et al 1994). In a mesic area similar to our study site, A. chilensis seedling survival and growth were positively associated with post-fire cover during the 2 years after plantation (Urretavizcaya et al 2017). In our study, however, this nursing effect appeared two seasons after acclimation.…”
Section: Discussionmentioning
confidence: 45%
“…However, in order to guarantee the establishment of the target species, restoration practices sometimes require additional microsite manipulation to avoid or diminish any deleterious biotic or micro-environmental effects on planted seedlings (Whisenant 1999). These effects are mainly caused by competition for soil water or nutrients by early successional herbaceous vegetation, excessive soil heating by higher incoming radiation reaching denuded soils, or by the lack of nurse plants (generally shrubs or half-shrubs) that protect seedlings from excessive temperature fluctuations (Padilla and Pugnaire 2006;Urretavizcaya et al 2017). Forest-productivity research has identified interactions between competing vegetation and logging debris left after forest harvesting.…”
Section: Introductionmentioning
confidence: 99%
“…Del Campo et al (2006) mostraron a su vez, que dentro de los protectores se produce un efecto de condensación, que puede mejorar la humedad alrededor de las plantas. En este estudio la protección artificial sólo tuvo un efecto negativo en el sitio mésico sobre el crecimiento en diámetro (de un 20% respecto a plantas sin protección), mientras que en la supervivencia y el incremento en altura no se observó efecto, esto último coincidiendo con lo reportado para el ciprés por Urretavizcaya et al (2017).…”
Section: Efectos Sobre La Supervivenciaunclassified
“…Estos resultados coinciden con la tendencia reportada para el crecimiento en altura de ciprés por Urretavizcaya et al (2017) y de ambas especies por Pafundi et al (2016).…”
Section: Efectos Sobre El Crecimientounclassified
See 1 more Smart Citation